A method for preparing magnetic chitosan microspheres that selectively adsorb [Au(S2O3)2]3- and its application.

CN118491489BActive Publication Date: 2026-10-30GRINM RESOURCES & ENVIRONMENT TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410576048.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2026-10-30
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

[0004]本申请提供一种选择性吸附[Au(S2O3)2]3-的磁性壳聚糖微球的制备方法及其应用,以解决硫代硫酸盐浸出金的环境复杂性及离子干扰,导致的浸出金难以回收的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118491489B_ABST
    Figure CN118491489B_ABST
Patent Text Reader

Abstract

The application provides a kind of selective adsorption [Au (S2O3) 2] 3‑ The application relates to a preparation method and application of magnetic chitosan microspheres, and belongs to the technical field of precious metal recovery. Fe3O4 is added into a chitosan solution, stirred uniformly, and then dropped into a NaOH solution to prepare the magnetic chitosan microspheres. The magnetic chitosan microspheres are dispersed into deionized water to obtain a mixed solution, the pH value of the mixed solution is adjusted to 10, and then epichlorohydrin is added for first cross-linking to obtain a first precursor. The first precursor is added into a [Au (S2O3) 2] 3‑ solution for sufficient stirring and mixing. After uniform mixing, glutaraldehyde is added for second cross-linking to obtain a second precursor. The second precursor is washed to neutral, and [Au (S2O3) 2] 3‑ ions are eluted. Then, the second precursor is soaked in 1 mol / L ‑1 NaOH for 1 h, washed to neutral, vacuum dried, and [Au (S2O3) 2] 3‑ magnetic chitosan microspheres with selective adsorption performance are obtained. 3‑ The magnetic chitosan microspheres with selective adsorption performance prepared by the above method have high stability, the raw materials are cheap, and the magnetic chitosan microspheres can be used for selective adsorption of [Au (S2O3) 2] 4+ in a Cu-NH 3‑ leaching system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of precious metal recycling technology, and in particular to a method for selectively adsorbing [Au(S2O3)2]. 3- Preparation method and application of magnetic chitosan microspheres. Background Technology

[0002] Thiosulfate leaching is a highly efficient metal extraction method with several advantages. Its non-toxicity, low cost, and rapid leaching rate make it a promising alternative to cyanide-based gold extraction. Furthermore, it can efficiently extract gold from ores or waste at a lower cost compared to traditional cyanide methods. However, in actual leaching environments, the complex associated conditions of gold deposits, coupled with the addition of various synergistic leaching agents such as copper and ammonium to improve leaching efficiency, can lead to ion interference, resulting in [Au(S₂O₃)₂]... 3- The complex environment has a significant impact on the selective adsorption of gold.

[0003] Due to the simultaneous existence of steric hindrance, ionic group volume, and ionic interference issues, gold recovery using activated carbon under these conditions is difficult. Therefore, a method for gold recovery in Cu-NH4+ system is urgently needed. 4+ Materials with high selective adsorption of gold in leaching systems are used to improve the adsorption effect of gold. Summary of the Invention

[0004] This application provides a method for selectively adsorbing [Au(S2O3)2]. 3- The preparation method and application of magnetic chitosan microspheres are proposed to solve the problem of difficult gold recovery caused by the environmental complexity and ion interference in gold leaching with thiosulfate.

[0005] In a first aspect of this application, a method for selectively adsorbing [Au(S2O3)2] is provided. 3- A method for preparing magnetic chitosan microspheres, the method comprising the following steps:

[0006] Step 1: Add Fe3O4 to the chitosan solution, stir well, and then add dropwise to a concentration of 2 mol / L. -1 Magnetic chitosan microspheres were prepared in NaOH solution;

[0007] Step 2: Disperse the magnetic chitosan microspheres in deionized water to obtain a mixed solution. After adjusting the pH of the mixed solution to 10, add epichlorohydrin to perform the first crosslinking to obtain the first precursor.

[0008] Step 3: Add the first precursor to [Au(S2O3)2] 3- In solution, [Au(S2O3)2] 3-The mixture was thoroughly stirred and mixed with chitosan amino groups. After the mixture was homogeneous, glutaraldehyde was added for a second crosslinking process to obtain the second precursor.

[0009] Step 4: Wash the second precursor alternately with ethanol and deionized water until neutral, then wash with 1 mol / L... -1 Eluting [Au(S2O3)2] with sulfuric acid 3- Ions, until [Au(S2O3)2] is undetectable. 3- Ions, then use 1 mol / L -1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres.

[0010] In one optional embodiment of this application, in step 1, the chitosan solution is a mixed solution of chitosan and 2.0% acetic acid solution, and the concentration of the chitosan solution is 2-3 wt%.

[0011] In one optional embodiment of this application, in step 1, the mass ratio of Fe3O4 to chitosan is 0.1 to 0.15:1.

[0012] In one optional embodiment of this application, in step 2, the magnetic chitosan microspheres are dispersed in deionized water by ultrasonic dispersion, the ultrasonic dispersion time is at least 5 minutes, and the ultrasonic power is 90w-120w.

[0013] In one optional embodiment of this application, in step 2, the ratio of epichlorohydrin to chitosan is 0.5-0.6 mL / g.

[0014] In one optional embodiment of this application, in step 2, the time for the first crosslinking is at least 3 hours.

[0015] In an optional embodiment of this application, in step 3, the first precursor and [Au(S2O3)2] are... 3- The molar ratio of the solution is 2:1 to 4:1.

[0016] In one optional embodiment of this application, in step 3, the [Au(S2O3)2] 3- The mixing time with chitosan amino groups should be at least 6 hours.

[0017] In one optional embodiment of this application, in step 3, the crosslinking temperature for the second crosslinking using glutaraldehyde is 60-65°C, and the crosslinking time is at least 3 hours.

[0018] A second aspect of this application provides a method for selectively adsorbing [Au(S2O3)2]. 3- The application of magnetic chitosan microspheres is characterized by the selective adsorption of [Au(S2O3)2]. 3- Magnetic chitosan microspheres are used for selective adsorption of Cu-NH4+. 4 + [Au(S2O3)2] in the leaching system 3- ;

[0019] The selective adsorption of [Au(S2O3)2] 3- The magnetic chitosan microspheres are prepared by any one of the methods described in the first aspect above.

[0020] This application includes the following advantages: This application provides a method for selectively adsorbing [Au(S2O3)2]. 3- The preparation method and application of magnetic chitosan microspheres: Fe3O4 is added to a chitosan solution, stirred evenly, and then added dropwise to a concentration of 2 mol / L. -1 Magnetic chitosan microspheres were prepared in NaOH solution; the magnetic chitosan microspheres were dispersed in deionized water to obtain a mixed solution; the pH of the mixed solution was adjusted to 10, and epichlorohydrin was added for the first crosslinking to obtain a first precursor; the first precursor was added to [Au(S2O3)2] 3- In solution, [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups. After homogeneity, glutaraldehyde was added for a second crosslinking to obtain the second precursor. The second precursor was then washed alternately with ethanol and deionized water until neutral, and then washed with 1 mol / L... -1 Eluting [Au(S2O3)2] with sulfuric acid 3- Ions, until [Au(S2O3)2] is undetectable. 3- Ions, then use 1 mol / L -1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres were prepared as described above. These microspheres selectively adsorbed [Au(S₂O₃)₂]. 3- The magnetic chitosan microspheres exhibit strong stability, are made from inexpensive raw materials, and are inexpensive to prepare, making them suitable for industrial production. The prepared microspheres selectively adsorb [Au(S2O3)2]. 3- Magnetic chitosan microspheres are used for selective adsorption of Cu-NH4+. 4+ [Au(S2O3)2] in the leaching system 3- . Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This application provides a method for selectively adsorbing [Au(S2O3)2]. 3- A flowchart illustrating the steps involved in preparing magnetic chitosan microspheres;

[0023] Figure 2 This application provides a method for selectively adsorbing [Au(S2O3)2]. 3- Image of magnetic chitosan microspheres;

[0024] Figure 3 This refers to the selective adsorption of [Au(S2O3)2] prepared in Example 1 of this application. 3- Adsorption effect diagram of magnetic chitosan microspheres;

[0025] Figure 4 This refers to the selective adsorption of [Au(S2O3)2] prepared in Example 2 of this application. 3- Adsorption effect diagram of magnetic chitosan microspheres. Detailed Implementation

[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its application or use. Based on the embodiments of this application, any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining features of this application with other prior art, falls within the protection scope of this application. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this application.

[0027] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of this application and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0028] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and equipment should be considered part of the specification.

[0029] Thiosulfate leaching is a highly efficient metal extraction method with several advantages. Its non-toxicity, low cost, and rapid leaching rate make it a promising alternative to cyanide-based gold extraction. Furthermore, it can efficiently extract gold from ores or waste at a lower cost compared to traditional cyanide methods. However, in actual leaching environments, the complex associated conditions of gold deposits, coupled with the addition of various synergistic leaching agents such as copper and ammonium to improve leaching efficiency, can lead to ion interference, resulting in [Au(S₂O₃)₂]... 3- The complex environment has a significant impact on the selective adsorption of gold.

[0030] Due to the simultaneous existence of steric hindrance, ionic group volume, and ionic interference issues, specifically as follows: In thiosulfate leachate [Au(S₂O₃)₂]... 3- The influence of the coordination group charge and molecular structure spatial effects leads to a large distance between gold atoms and the surface of activated carbon, making adsorption difficult. Furthermore, the high charge number and hydration energy of this complex ion make gold recovery under these conditions challenging using activated carbon. Therefore, a method for gold recovery under Cu-NH4+ conditions is urgently needed. 4+ Materials with high selective adsorption of gold in leaching systems are used to improve the adsorption effect of gold.

[0031] Based on this, embodiments of this application provide a method for selectively adsorbing [Au(S2O3)2] in a first aspect. 3- A method for preparing magnetic chitosan microspheres, based on which magnetic chitosan microspheres can be prepared for use in Cu-NH4+. 4+ [Au(S2O3)2] exhibits selective adsorption of gold in the leaching system. 3- Magnetic chitosan microspheres, see Figure 1 , Figure 1 A selective adsorption method for [Au(S2O3)2] is provided in the embodiments of this application. 3- A schematic diagram of the preparation method, the method including the following steps:

[0032] Step 1: Add Fe3O4 to the chitosan solution, stir well, and then add it dropwise to a concentration of 2 mol / L. -1 Magnetic chitosan microspheres were prepared in NaOH solution;

[0033] Step 2: Disperse the magnetic chitosan microspheres in deionized water to obtain a mixed solution. After adjusting the pH of the mixed solution to 10, add epichlorohydrin to perform the first crosslinking to obtain the first precursor.

[0034] Step 3: Add the first precursor to [Au(S2O3)2] 3- In solution, [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups. After the mixture was homogeneous, glutaraldehyde was added for a second crosslinking process to obtain the second precursor.

[0035] Step 4: Wash the second precursor alternately with ethanol and deionized water until neutral, then wash with 1 mol / L... -1 Eluting [Au(S2O3)2] with sulfuric acid 3- Ions, until [Au(S2O3)2] is undetectable. 3- Ions, then use 1 mol / L -1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres.

[0036] In step 1 above, the chitosan solution is a mixture of chitosan and 2.0% acetic acid solution, and the concentration of the chitosan solution is 2-3 wt%. Optionally, the chitosan solution can be a mixture of chitosan and acetic acid solution. The mass ratio of Fe3O4 to chitosan is 0.1-0.15:1. Optionally, the mass ratio of Fe3O4 to chitosan can be 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.5:1, etc., and this mass ratio is selected according to actual needs.

[0037] In step 2 above, the magnetic chitosan microspheres from step 1 are dispersed in deionized water using ultrasonic dispersion. The ultrasonic dispersion time is at least 5 minutes, but can be 10 minutes, 15 minutes, 20 minutes, etc. The ultrasonic power is 90W-120W, but can be 90W, 100W, 110W, 120W, etc. The ultrasonic dispersion time and power are selected according to actual needs. Ultrasonic dispersion ensures that Fe3O4 in the magnetic chitosan microspheres is uniformly dispersed in the chitosan. After ultrasonic dispersion, the mixture is incubated at 50°C in a constant-temperature oscillator for 3 hours.

[0038] After shaking, the pH of the mixed solution was adjusted to 10 using a 1 mol / L NaOH solution. Epichlorohydrin was then added to the mixed solution to induce the first cross-linking of the magnetic chitosan microspheres with epichlorohydrin. Through a nucleophilic substitution reaction, an intramolecular cross-linked structure was formed, yielding the first precursor. The ratio of epichlorohydrin to chitosan was 0.5-0.6 mL / g, which could be 0.5 mL / g, 0.52 mL / g, 0.54 mL / g, 0.56 mL / g, 0.58 mL / g, 0.6 mL / g, etc., selected according to actual needs. The first cross-linking process should take at least 3 hours.

[0039] After the first crosslinking, the first precursor and [Au(S2O3)2] are crosslinked. 3- The molar ratio of the solution is 2:1 to 4:1, and the first precursor is added to [Au(S2O3)2]. 3- In solution, to make [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups to form [Au(S2O3)2] inside the microspheres. 3- The spatial structure for identification, wherein the first precursor is related to [Au(S2O3)2]. 3- The molar ratio of the solution can be 2:1, 3:1, 4:1, etc., with the first precursor reacting with [Au(S₂O₃)₂]. 3- The molar ratio of the solution is selected according to actual needs. [Au(S2O3)2] 3- The mixing time with the first precursor is at least 6 hours, but can be 8 hours, 9 hours, 10 hours, etc., depending on actual needs. In the embodiments of this application, both the first crosslinking and mixing operations are carried out at room temperature.

[0040] After mixing, glutaraldehyde is added for a second crosslinking process. Utilizing its electrophilic and nucleophilic properties, this increases the crosslinking density between molecules, thereby improving the stability of the chitosan microspheres and yielding the second precursor. The crosslinking temperature for the second crosslinking with glutaraldehyde is 60-65℃, but can be 60℃, 61℃, 62℃, 63℃, 64℃, 65℃, etc., and the crosslinking time is at least 3 hours, but can be 3 hours, 4 hours, 5 hours, etc. The crosslinking temperature and time for the second crosslinking with glutaraldehyde are determined based on actual requirements. During the second crosslinking process, glutaraldehyde can cure [Au(S2O3)2]. 3- The cavity structure that combines with the first cross-linked magnetic chitosan makes the cavity structure more stable, and a certain cross-linking temperature can accelerate the cross-linking reaction process.

[0041] In step 4, the second precursor is first washed alternately with ethanol and deionized water until neutral, which can thoroughly remove the solvent from the second precursor. Then, acid is used to remove [Au(S2O3)2] from the second precursor. 3- Ion elution thoroughly allows for the formation of selectively adsorbed [Au(S2O3)2] within the magnetic chitosan microspheres. 3- The hole structure of ions, when using 1 mol / L -1 Sulfuric acid will [Au(S2O3)2] 3- After ion elution, use alkali (1 mol / L) -1 Neutralize the residual acid (1 mol / L) with NaOH. -1 The sulfuric acid was used, and the [Au(S2O3)2] was washed with deionized water. 3- Magnetic chitosan microspheres were neutralized and vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres. Store them in a sealed, dry space, away from drafts.

[0042] This application provides an embodiment for selective adsorption of [Au(S2O3)2]. 3- The method for preparing magnetic chitosan microspheres involves adding Fe3O4 to a chitosan solution, stirring until homogeneous, and then adding dropwise to a concentration of 2 mol / L. -1 Magnetic chitosan microspheres were prepared in NaOH solution; the magnetic chitosan microspheres were dispersed in deionized water to obtain a mixed solution; the pH of the mixed solution was adjusted to 10, and epichlorohydrin was added for the first crosslinking to obtain a first precursor; the first precursor was added to [Au(S2O3)2] 3- In solution, [Au(S2O3)2] 3- The mixture was mixed with chitosan amino groups, and after thorough mixing, glutaraldehyde was added for a second crosslinking to obtain the second precursor. The second precursor was then washed alternately with ethanol and deionized water until neutral, and then washed with 1 mol / L... -1 Eluting [Au(S2O3)2] with sulfuric acid 3- Ions, until [Au(S2O3)2] is undetectable. 3- Ions, then use 1 mol / L -1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres. The [Au(S2O3)2] prepared as described above... 3- Magnetic chitosan microspheres exhibit strong stability, are made from inexpensive raw materials, and are inexpensive to prepare, making them suitable for industrial production.

[0043] A second aspect of this application provides a method for selectively adsorbing [Au(S2O3)2]. 3- The application of magnetic chitosan microspheres will enable the selective adsorption of [Au(S2O3)2]. 3- Magnetic chitosan microspheres are used for selective adsorption of Cu-NH4+. 4+ [Au(S2O3)2] in the leaching system 3- The above selective adsorption of [Au(S2O3)2] 3- The magnetic chitosan microspheres are prepared by any one of the methods described in the first aspect above.

[0044] To enable those skilled in the art to more clearly understand this application, the following examples illustrate a selective adsorption method for [Au(S2O3)2] described in this application. 3- The preparation method and application of magnetic chitosan microspheres are described in detail.

[0045] Example 1

[0046] Step 1: Add Fe3O4 to a 2.0% chitosan solution (chitosan acetic acid solution) at a Fe3O4:chitosan mass ratio of 0.15:1. After stirring evenly, a magnetic chitosan solution is obtained. Add the magnetic chitosan solution dropwise to a 2 mol / L solution. -1 Magnetic chitosan microspheres were prepared in NaOH solution;

[0047] Step 2: Disperse the magnetic chitosan microspheres in deionized water and sonicate them for 10 min under an ultrasonic intensity of 100 W. Then, treat them in a constant temperature shaker at 50 °C for 3 h to obtain a mixed solution. Adjust the pH of the mixed solution to 10, and add epichlorohydrin at a ratio of 0.5 mL / g to chitosan to carry out the first crosslinking for 3 h to obtain the first precursor.

[0048] Step 3: According to the first precursor and [Au(S2O3)2] 3- The molar ratio of the solution is 2:1, and the first precursor is added to [Au(S2O3)2]. 3- In solution, [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups. After mixing for 8 hours, glutaraldehyde was added and the mixture was cross-linked for a second time at 60°C for 3 hours to obtain the second precursor.

[0049] Step 4: Wash the second precursor with ethanol and deionized water until neutral, then wash with 1 mol / L... -1 [Eluting Au(S2O3)2 with sulfuric acid] 3- Ions, until Au(S2O3)2 is undetectable. 3- Ions, then use 1 mol / L-1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres.

[0050] Example 2

[0051] Step 1: Add Fe3O4 to a 2.5% chitosan solution (chitosan acetic acid solution) at a Fe3O4:chitosan mass ratio of 0.12:1. After stirring evenly, a magnetic chitosan solution is obtained. Add the magnetic chitosan solution dropwise to a 2 mol / L solution. -1 Magnetic chitosan microspheres were prepared in NaOH solution;

[0052] Step 2: Disperse the magnetic chitosan microspheres in deionized water and sonicate them for 10 min under an ultrasonic intensity of 110 W. Then, treat them in a constant temperature shaker at 50 °C for 3 h to obtain a mixed solution. Adjust the pH of the mixed solution to 10, and add epichlorohydrin at a ratio of 0.54 mL / g to chitosan to carry out the first crosslinking for 3 h to obtain the first precursor.

[0053] Step 3: According to the first precursor and [Au(S2O3)2] 3- The molar ratio of the solution is 3:1, and the first precursor is added to [Au(S2O3)2]. 3- In solution, [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups. After mixing for 10 hours, glutaraldehyde was added and the mixture was cross-linked for a second time at 60°C for 4 hours to obtain the second precursor.

[0054] Step 4: Wash the second precursor with ethanol and deionized water until neutral, then wash with 1 mol / L... -1 Eluting [Au(S2O3)2] with sulfuric acid 3- Ions, until [Au(S2O3)2] is undetectable. 3- Ions, then use 1 mol / L -1 After soaking in NaOH for 1 hour, the solution was washed with deionized water until neutral, and then vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres.

[0055] The selective adsorption of [Au(S2O3)2] prepared in Example 1 above 3- For a physical image of the magnetic chitosan microspheres, please refer to [link / reference]. Figure 2 .

[0056] Example 3

[0057] The selective adsorption of [Au(S2O3)2] prepared in Examples 1 and 2 above was used. 3- Magnetic chitosan microspheres are manufactured according to the chitosan formula: n([Au(S2O3)2] 3- The molar ratio of c(Au) to c(Cu) was 2:1, and the solutions were used for gold adsorption in the following three thiosulfate solutions. The adsorption was carried out at room temperature with stirring at 200 r / min for 24 h. The solutions were: solution 1: c(Au) = 25 mg / L, c(Cu) = 402 mg / L; solution 2: c(Au) = 25 mg / L, c(Cu) = 313 mg / L; solution 3: c(Au) = 25 mg / L, c(Cu) = 211 mg / L.

[0058] Before the adsorption experiment, the initial concentrations of Au and Cu in the thiosulfate solution are denoted as C0. After the adsorption experiment, the concentrations of Au and Cu remaining in the thiosulfate solution are denoted as C1. The adsorption rate is calculated as follows: Adsorption rate = (C0 - C1) / C0 * 100%.

[0059] Adsorption results are as follows Figure 3 , Figure 4 As shown, Figure 3 This refers to the selective adsorption of [Au(S2O3)2] prepared in Example 1 of this application. 3- Adsorption effect diagram of magnetic chitosan microspheres. Figure 4 This refers to the selective adsorption of [Au(S2O3)2] prepared in Example 2 of this application. 3- Adsorption effect diagram of magnetic chitosan microspheres.

[0060] Depend on Figure 3 and Figure 4 It can be seen that, in Figure 3 In Example 1, the selective adsorption of [Au(S2O3)2] was prepared. 3- Magnetic chitosan microspheres for Cu-NH 4+ In the leaching system, [Au(S2O3)2] 3- The adsorption rates of all components were above 95%, reaching a maximum of 98.7%, while the adsorption rates for Cu were all below 10%. Figure 4 In Example 2, the selective adsorption of [Au(S2O3)2] was prepared. 3- Magnetic chitosan microspheres for Cu-NH 4+ In the leaching system, [Au(S2O3)2] 3- The adsorption rates of [Au(S2O3)2] were all above 95%, reaching a maximum of 98.2%, while the adsorption rates of Cu were all below 10%. In solutions 1, 2, and 3, the Cu content was significantly higher than that of Au, with the order being solution 1 > solution 2 > solution 3. Generally, it is believed that higher concentrations are more easily adsorbed, but the selective adsorption of [Au(S2O3)2] prepared in this application embodiment is not as good.3- The magnetic chitosan microspheres still exhibit high adsorption capacity for Au, indicating that the selective adsorption of [Au(S2O3)2] prepared in the embodiments of this application is effective. 3- Magnetic chitosan microspheres for Cu-NH 4+ In the leaching system, [Au(S2O3)2] 3- It has high selective adsorption capacity and is of great theoretical and economic significance for the development of green gold extraction from thiosulfate.

[0061] The above describes a selective adsorption method for [Au(S2O3)2] provided in this application. 3- The preparation method and application of magnetic chitosan microspheres are described in detail. Specific examples are used to illustrate the principle and implementation of this application. The above description of the embodiments is only for the purpose of helping to understand the method and core idea of ​​this application. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of ​​this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A selective adsorption method for [Au(S2O3)2] 3- The application of magnetic chitosan microspheres is characterized by, The selective adsorption of [Au(S2O3)2] 3- Magnetic chitosan microspheres are used for selective adsorption of Cu-NH4+. 4+ [Au(S2O3)2] in the leaching system 3- ; The selective adsorption of [Au(S2O3)2] 3- The preparation method of magnetic chitosan microspheres includes the following steps: Step 1: Add Fe3O4 to the chitosan solution, stir well, and then add it dropwise to a 2 mol / L NaOH solution to obtain magnetic chitosan microspheres; Step 2: Disperse the magnetic chitosan microspheres in deionized water to obtain a mixed solution. After adjusting the pH of the mixed solution to 10, add epichlorohydrin to perform the first crosslinking to obtain the first precursor. Step 3: Add the first precursor to [Au(S2O3)2] 3- In solution, [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups. After the mixture was homogeneous, glutaraldehyde was added for a second cross-linking process to obtain the second precursor. Step 4: Wash the second precursor alternately with ethanol and deionized water until neutral, then elute with 1 mol / L sulfuric acid to remove [Au(S2O3)2]. 3- Ions, until [Au(S2O3)2] is undetectable. 3- The ions were then soaked in 1 mol / L NaOH for 1 h, washed with deionized water until neutral, and vacuum dried to obtain selectively adsorbed [Au(S2O3)2]. 3- Magnetic chitosan microspheres; The first precursor is added to [Au(S2O3)2] 3- In solution, to make [Au(S2O3)2] 3- The mixture was thoroughly stirred and mixed with chitosan amino groups to form [Au(S2O3)2] inside the microspheres. 3- Recognizing spatial structure; During the second crosslinking process, glutaraldehyde can be used to cure [Au(S2O3)2]. 3- The cavity structure, which is combined with the first cross-linked magnetic chitosan, makes the cavity structure more stable. The first precursor and [Au(S2O3)2] 3- The molar ratio of the solution is 2:1 to 4:1; The [Au(S2O3)2] 3- The mixing time with chitosan amino groups should be at least 6 hours.

2. The selective adsorption of [Au(S2O3)2] according to claim 1. 3- The application of magnetic chitosan microspheres is characterized by, In step 1, the chitosan solution is a mixture of chitosan and acetic acid solution, and the concentration of the chitosan solution is 2-3 wt%.

3. The selective adsorption of [Au(S2O3)2] according to claim 1 3- The application of magnetic chitosan microspheres is characterized by, In step 1, the mass ratio of Fe3O4 to chitosan is 0.1~0.15:

1.

4. The selective adsorption of [Au(S2O3)2] according to claim 1. 3- The application of magnetic chitosan microspheres is characterized by, In step 2, the magnetic chitosan microspheres are dispersed in deionized water by ultrasonic dispersion for at least 5 minutes and with an ultrasonic power of 90 W-120 W.

5. The selective adsorption of [Au(S2O3)2] according to claim 1 3- The application of magnetic chitosan microspheres is characterized by, In step 2, the ratio of epichlorohydrin to chitosan is 0.5-0.6 mL / g.

6. The selective adsorption of [Au(S2O3)2] according to claim 1. 3- The application of magnetic chitosan microspheres is characterized by, In step 2, the first crosslinking time is at least 3 hours.

7. The selective adsorption of [Au(S2O3)2] according to claim 1 3- The application of magnetic chitosan microspheres is characterized by, In step 3, the crosslinking temperature for the second crosslinking using glutaraldehyde is 60-65 °C, and the crosslinking time is at least 3 h.

Citation Information

Patent Citations

  • Method for preparing heavy metal ion imprinting magnetic chitosan adsorbent

    CN106552590A

  • Thiourea imprinting resin, preparation method thereof and application of thiourea imprinting resin to gold adsorption

    CN109926028A

  • Method for selectively adsorbing gold in copper ion-ethylenediamine-thiosulfate leaching system

    CN115888668A